Metal–ligand cooperativity in the soluble hydrogenase-1 from Pyrococcus furiosus. Issue 32 (6th August 2020) - Vansuch, Gregory E.; Wu, Chang-Hao; Haja, Dominik K.; Blair, Soshawn A.; Chica, Bryant; Johnson, Michael K.; Adams, Michael W. W.; Dyer, R. Brian
Abstract : Metal–ligand cooperativity is an essential feature of bioinorganic catalysis. Abstract : Metal–ligand cooperativity is an essential feature of bioinorganic catalysis. The design principles of such cooperativity in metalloenzymes are underexplored, but are critical to understand for developing efficient catalysts designed with earth abundant metals for small molecule activation. The simple substrate requirements of reversible proton reduction by the [NiFe]-hydrogenases make them a model bioinorganic system. A highly conserved arginine residue (R355) directly above the exogenous ligand binding position of the [NiFe]-catalytic core is known to be essential for optimal function because mutation to a lysine results in lower catalytic rates. To expand on our studies of soluble hydrogenase-1 from Pyrococcus furiosus ( Pf SH1), we investigated the role of R355 by site-directed-mutagenesis to a lysine (R355K) using infrared and electron paramagnetic resonance spectroscopic probes sensitive to active site redox and protonation events. It was found the mutation resulted in an altered ligand binding environment at the [NiFe] centre. A key observation was destabilization of the Nia 3+ –C state, which contains a bridging hydride. Instead, the tautomeric Nia + –L states were observed. Overall, the results provided insight into complex metal–ligand cooperativity between the active site and protein scaffold that modulates the bridging hydride stability and the proton inventory, which should prove valuable to design principles for efficient bioinspired catalysts.